PERBANDINGAN DAN HUBUNGAN WILAYAH GEOGRAFIS DAN SARANA KESEHATAN PADA INSIDENSI SERTA PREVALENSI LEPRA DI KEPULAUAN MADURA - Eryta Deka Wulan Agustin; Sri Herlina; Rahma Triliana (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction : Leprosy is chronic infection caused by Mycobacterium leprae which can cause long-term disability. Paucibacillary (PB) and Multibacillary (MB) leprosy has high prevalence and incidence especially in Madura Island. One of the factor that influence isgeographical area that can make many patients not covered by health services that provide health facilities and medical professionals. The effect of geographic area to prevalence and incidence of leprosy in Madura Islands has never been studied.Method : Cross-sectional study with secondary data acquired from Health Profile of Sumenep Regency. Sample in this research were collected from data leprosy patien in 2014 – 2018 in Sumenep Regency and Poteran Island that taken by purposive sampling method. Results : There was comparison between health facilities and health workers in Sumenep and Poteran p=0,000. There was relation between health facilities and MB leprosy prevalence in Poteran 2014-2018 p=0,029. Health facilities and health workers had no relation with incidence and leprosy prevalence in Sumenep p=0,070 and p=0,099.Conclusion : There was relation between health facilities and MB leprosy prevalence in Poteran 2014-2018. There was relation between health workers in MB leprosy prevalence in Poteran Island at 2014-2018. Further research is needed to find other factors which affected on prevalence and incidence of leprosy. Keywords: Leprosy, Geographic Area, Incidence, Prevalence